2017
DOI: 10.5539/elt.v10n3p82
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of English Language Learning on Creative Thinking Skills: A Mixed Methods Case Study

Abstract: The purpose of this sequential explanatory mixed-methods case study was to investigate the effects of English language learning on creative thinking skills in the domains of fluency, flexibility, originality, and elaboration as measured with the Alternate Uses Test. Unlike the previous research studies that investigated the links between English language learning and cognitive skills and had large numbers of participants, this research study relied on small group of participants to provide detailed information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In writing, students need to be creative in getting varied ideas and perspectives. The creativity of the students could be strengthened by language instruction [15]. In this study, we focused on writing as one of the language skills.…”
Section: Creativitymentioning
confidence: 99%
“…In writing, students need to be creative in getting varied ideas and perspectives. The creativity of the students could be strengthened by language instruction [15]. In this study, we focused on writing as one of the language skills.…”
Section: Creativitymentioning
confidence: 99%
“…Maintaining consistency is very important in language acquisition. When students focus on small 15-minute study sessions regularly instead of spending several hours learning a language once a week or even once a month, the teacher thinks (Sehic, 2017). "Love it."…”
Section: Effective Language Learning With Blended Learningmentioning
confidence: 99%
“…Teachers and other learning communities can also use blended learning to refresh and improve current foreign language skills (Sehic, 2017). Here it is clear the proper role of the blended learning approach in schools.…”
Section: Effective Language Learning With Blended Learningmentioning
confidence: 99%
“…Likewise, Gurak-Ozdemir (2016) and Barker (2019) indicated that training teachers on creativity has a positive influence on enhancing their learners' creative abilities. Also, a case study conducted by Sehic (2017) concluded that students' creativity skills could be improved through language teaching and vice versa.…”
Section: Enhancing Creativity In Educationmentioning
confidence: 99%